Ethical Issues in Dysphagia Management - Leslie, Paula; Lisiecka, Dominika (Seminars in Speech and Language, 2020)
Dysphagia management is complex and requires balancing individuals' preferences, quality of life, and medical consequences. Ethical challenges are not uncommon given the complexity of dysphagia. Professionals must engage in ethical reflection and shared decision-making when managing dysphagia. Recognizing one's own presuppositions and beliefs may be fundamental to ensuring an ethical approach. The goal of this article is to apply principles of ethics using hypothetical case studies of dysphagia. To this end, we will describe the challenges of working with the disorder of dysphagia; the influence of culture on decision-making about eating and feeding; the importance of information disclosure and respect for individuals' refusal of recommendations; and the interplay of ethical reflection, evidence, and clinical judgment when making complex dysphagia management decisions. These concepts should be kept in mind to ensure compassionate and competent care of the person with eating, drinking, or swallowing problems and their family caregivers.
Keywords: ethics; decision-making; consent; dysphagia; discretion